Transformation of the Roman rural landscape in Central Dalmatia (Roman Dalmatia) – from residential villas to administrative centers - Zeman, Maja (2012)
In the context of the ongoing discussion about the modes of transformation of the ancient rural landscape, the Croatian scholarship chose an awkward approach, studying the earliest phases of the Dalmatian villas in a very selective manner and with primary interest in the early-Christian and early medieval structures that have developed on top of Roman villas sites. This approach proved to be inadequate in several respects. Thus, this paper represents an effort to reverse the usual perspective applied to Dalmatian villas, and to demonstrate the way in which the analysis of architectural forms and plans of specific Roman/Late Roman villa-complexes, features of which obviously indicate the function and possibly even the ownership over a major properties, should be used as a necessary starting point in any research of the continuity and change in the organization of the rural landscape. Selected case studies are the sites situated in the coastal area of juridical convent of Salona, located between modern town of Trogir (Roman Tragurium) and the River Krka (Titius), where ancient Hyllis (today Bosiljina) peninsula and the territory associated with Roman municipium Rider are situated. Selected villas differ in typology and partly chronologically, as well as in the path of their future development. But, positioned on the main Roman communication routes of the Eastern Adriatic they held an important strategic position and undoubtedly a prominent position in the organization of the surrounding area. Today, their importance can be deduced according to variety of sources, but, in a large scale, from their architectural features and from the features of different late-antique or early medieval structures that have developed on the site.
ENG